2012
DOI: 10.1073/pnas.1117313109
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic diversity is generated by distinct evolutionary mechanisms in African trypanosome species

Abstract: Antigenic variation enables pathogens to avoid the host immune response by continual switching of surface proteins. The protozoan blood parasite Trypanosoma brucei causes human African trypanosomiasis ("sleeping sickness") across sub-Saharan Africa and is a model system for antigenic variation, surviving by periodically replacing a monolayer of variant surface glycoproteins (VSG) that covers its cell surface. We compared the genome of Trypanosoma brucei with two closely related parasites Trypanosoma congolense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
206
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(221 citation statements)
references
References 32 publications
3
206
0
9
Order By: Relevance
“…Analyses of the genomic databases of T. cruzi (CL Brener) (39), T. vivax (Y486), and T. congolense (IL-3000) (40) showed that the presence of two tRNA-Sec genes is conserved across the genus Trypanosoma (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of the genomic databases of T. cruzi (CL Brener) (39), T. vivax (Y486), and T. congolense (IL-3000) (40) showed that the presence of two tRNA-Sec genes is conserved across the genus Trypanosoma (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…African animal typanosomiasis causes serious losses in Cattle, sheep, goats, pigs, horses and many other host animals [1] , thus reducing the source of animal protein [2] , and ultimately contributing to food insecurity in the region. The development of a vaccine for the treatment of the disease is becoming increasingly difficult due to the problem of antigenic variation [3] , hence the dependence on chemotherapeutic agents to control the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic analyses have challenged this assumption, revealing significant differences between the VSG archives in the three species (75,84). Whole genome comparisons revealed that in T. congolense there is no equivalent of the T. brucei a-VSG subfamily; in contrast, there are two b-VSG subfamilies and a much greater range of distinct C-terminal domains (15-20 CTD types, each of which are found to be associated with particular VSG subtypes, in contrast to the single CTD found in T. brucei).…”
Section: What Do We Know About Antigenic Variation In Other Species Omentioning
confidence: 99%
“…It is clear that we have only just begun to examine the processes that shape and diversify the VSG archive, and do not fully understand the events that operate during replication, over the course of an infection and through the life cycle. Understanding this will determine the extent to which archives compare or diverge in extant trypanosome isolates (47,84). Just as importantly, we do not yet understand if and how these largely silent processes within the archive intersect with our growing understanding of how VSGs are recombined into the BES.…”
Section: The Genomic Components Of Antigenic Variation In Trypanosomamentioning
confidence: 99%